Perceived enablers of upward mobility of female employees in a financial services organisation - Moyana, Matilda (Organisational Psychology, 2019)
Research purpose: The purpose of the study was to identify enablers of upward mobility into middle and senior management positions among female employees in a particular organisation of the financial services sector. Motivation for the study: In the South African context, it was demonstrated that although women comprised 51.2% of the adult population in 2016 (numbering approximately 28 53 million and were supported by progressive legislation and had a 45.8% representation in the workforce, they occupied a relatively low percentage of management positions. South African research on enabling factors that are important for the career progression of women has been conducted in national banks, South African business schools and the education sector. The findings revealed that enabling factors for the career progression of women include supervisor support, education, social networks, top management support and family-friendly policies. Identifying such enabling factors is important since there is strong evidence that the promotion of women into management roles is not only morally right but can also increase business performance. Research design and method: The research design was descriptive. A cross-sectional qualitative approach was used to collect the primary data. Data analysis was exploratory. Since the aim of the study was to investigate perceptions of female employees in middle and senior management positions through their lived experiences, in-depth one-on-one interviews with 15 female employees were completed. Purposive sampling was used to secure the research participant sample. The results from the qualitative data were collected and analysed using content analysis. Themes extracted were used to report the findings of the study. Findings: The results show that organisational support structures (i.e. supervisor support and career development), employee competence (i.e. education and social networks) and strategic interventions (i.e. top management support and family-friendly policies) are important factors for the career progression of women in the financial services sector under investigation. Practical implications: The enabling factors identified in this study can be used to enhance interventions for the advancement of promotion of women into senior management positions. Contribution: The findings of the study indicate that organisational support structures, employee competence and strategic interventions are important factors for the career progression of women, adding to the discourse of the promotion of women into senior management positions.